Superhydrophobic and elastic 3D conductive sponge made from electrospun nanofibers and reduced graphene oxide for sweatproof wearable tactile pressure sensor. (16th September 2021) - Liang, Zhipeng; Zhang, Huanxia; Huang, Runzhou; Xu, Tao; Fong, Hao
Abstract: Herein, we report an innovative method to produce three-dimensional (3D), elastic, and conductive nanofibrous sponges with high sensitivity, great mechanical properties, and sweatproof feature for wearable tactile pressure sensor. The 3D sponges were prepared by assembling the shortened polyacrylonitrile/polyimide (PAN/PI) electrospun nanofibers and reduced graphene oxide (rGO) nanosheets. In specific, the PAN/PI nanofibers and graphene oxide (GO) nanosheets were mixed in aqueous circumstance first and then freeze dried to form a 3D porous sponge. Subsequently, the sponge was thermally treated at 100 °C and 210 °C successively to reduce the GO nanosheets to conductive rGO nanosheets. Thereafter, the polydimethylsiloxane (PDMS) treatment was carried out to provide the sponge with elasticity/robustness and hydrophobicity. Upon varying the amount of rGO, three types of sponges were fabricated to study their mechanical and electrical properties. The obtained 3D conductive sponge with the most rGO amount (3-rGO/NF) possessed light weight (11.50 mg/cm 3 ) and high porosity (99.23%). The mechanical strength and current change ratio during the cyclic compression process were investigated, and the results were closely correlated with the amount of rGO existed in the sponge. The 3-rGO/NF had the largest current change ratio when compressed, leading to the highest sensitivity even at a relatively small compressive strain. It is important to note that the prepared 3D conductive sponges were sensitive, bendable, and sweatproof, which would be particularly suitable for making wearable tactile pressure sensors. Graphical abstract: Image 1 Highlights: Superhydrophobic and elastic 3D conductive nanofibrous sponges were fabricated. The sponges were made from electrospun PAN/PI nanofibers and GO/rGO nanosheets. Tunable conductivity and high sensitivity could be achieved for these sponges. The PDMS treatment improved mechanical robustness/elasticity and hydrophobicity. The 3D sponges exhibited excellent performance for making wearable pressure sensors.